A Study on the Knowledge And Practices of Childhood Diarrhoeal Diseases Management Among Mothers in the Wa District, Upper West Region. Ghana - Owusu, E. (University of Ghana, 1997)
This study was undertaken in the Wa District of the Upper West region o f Ghana during the period o f 5th April to 15th May 1997 in six (6) sub-districts. The study was to answer the following question: “ What level o f knowledge do mothers in the Wa District have about diarrhoea, it’s causes, effects, appropriate home treatment and prevention, and what they practice during episodes o f diarrhoea among young children” There have been concerns expressed at the district and regional level sectors o f the Ministry o f Health about the high prevalence and incidence o f diarrhoeal diseases particularly among young children in the Wa district with high fatality rates despite efforts put in by the District Health Management Team to intensify health education activities in the district. Though there had been previous attempt to carry out a study to answer this question, the study was linked up to a nutritional survey carried out by the Nutrition Unit o f the Regional Health Administration and only concentrated on a few mothers who attended the nutrition rehabilitation center in the region. This study is therefore intended to provide further information on what mothers in the district know and practice about diarrhoeal diseases management for young children, with the view o f using the findings o f the study to assist the District Health Administration and other health -related agencies in the district and the region in programming appropriate health education and promotion strategies to reduce diarrhoeal- related diseases and improve promote the general health o f young children in the district. The study was conducted with the broad objective o f finding out what women in the Wa district know about childhood diarrhoeal diseases and what they practice to manage the disease during episodes. The specific objectives of the study are: 1) To determine the level of information that mothers in the study area have about diarrhoeal diseases. 2) To identify any gap between what the mothers know and what they are expected to know about diarrhoeal diseases in young children. 3) To find out the management practices that mothers adopt during diarrhoea episodes in young children. 4) To recommend appropriate health intervention strategies and programmes for implementation to reduce the high prevalence o f diarrhoeal diseases among young children in the district. The sample size for the study was 210 mothers o f the Wa district who have children up to two (2) years. A household survey was conducted to interview mothers who were selected by means o f simple random sampling technique. A structured questionnaire was used as data collection tool to obtain information from the mothers on diarrhoeal diseases. The main variables o f study were: 1). Knowledge about diarrhoeal diseases, causes, effects, treatment and prevention. 2). Diarrhoea Management practices concerning treatment, feeding, breastfeeding and prevention. 3). Sources of information on childhood diarrhoeal diseases. The major findings of the study were as follows: 1) Mothers in the study area could adequately describe childhood diarrhoea but have limited knowledge about the causes, effects and dangers of diarrhoeal diseases on the child. 2) A significant proportion o f mothers in the study area strongly believe that supernatural forces such as witches and evil spirits could cause childhood diarrhoea. 3) More than half o f the mothers treat the child with diarrhoea at home. Among the various home treatment practices they adopt include enema administration, administration of various kinds of drugs obtained from the local market and the administration o f herbal concoctions. 4) A greater number o f mothers are aware o f the value o f continued feeding and breastfeeding the child and adopt the practice during diarrhoeal episode. 5) Though many mothers have ever heard of Oral Rehydration Salt (sachets) as an effective treatment o f childhood diarrhoea, quite a number o f the mothers have never used it to treat their children. Based on the findings o f the study, the following recommendations are suggested for implementation. 1) Health Education and Promotion activities on diarrhoeal diseases in the study area should emphasize on teaching mothers about the “germ theory” o f disease causation, effects, dangers as well as appropriate home management practices and prevention o f diarrhoeal diseases. 2) The value of the use o f O.R.S should be emphasized for mothers to appreciate it’s use for treating their children with diarrhoea at home even before taking the child to a health facility. 3) Outreach Health services should be extended to those communities or villages in the study area which are far away from the existing health facilities, and during each outreach session, a brief teaching on childhood diarrhoea should be given to mothers by the health team. 4) Misconceptions and beliefs about diarrhoeal diseases that are strongly held by mothers in the study area should be disabused with correct and adequate information about diarrhoeal diseases. 5) O.R.T comers or centres should be established in all health centres in the district which could be used as training or teaching centres for mothers who use the health facilities. Where possible some of the mothers could be used as resource persons in O.R.T training for mothers. 6) Health personnel particularly, Community and Public Health Nurses who do home visiting, should use the opportunity to teach mothers in their own homes about diarrhoea and it’s appropriate home management. 7) Mothers’ Clubs should be formed in all communities/villages so that mothers could share together information and experiences on diarrhoea management practices and other child survival activities.
Thesis (MPH)-University of Ghana